The big disconnect : protecting childhood and family relationships in the digital age - Steiner-Adair, Catherine; Barker, Teresa (New York : Harper, 2013)
In this book the author offers insights and advice that can help parents achieve greater understanding, authority, and confidence as they come up against the tech revolution and how families can combat the disconnection we are experiencing from our extreme device dependence.
Have iPads replaced conversation at the dinner table? What do infants observe when their parents are on their smartphones? Should you be your child's Facebook friend? As the focus of family has turned to the glow of the screen, children constantly texting their friends, parents working online around the clock, everyday life is undergoing a massive transformation. Easy availability to the Internet and social media has erased the boundaries that protect children from the unsavory aspects of adult life. Parents often feel they are losing a meaningful connection with their children. Children are feeling lonely and alienated. The digital world is here to stay, but what are families losing with technology's gain? As the author, a clinical psychologist, explains, families are in crisis around this issue, and even more so than they realize. Not only do chronic tech distractions have deep and lasting effects, but children desperately need parents to provide what tech cannot: close, significant interactions with the adults in their lives. Drawing on real-life stories from her clinical work with children and parents, and her consulting work with educators and experts across the country, she offers insights and advice that can help parents achieve greater understanding, authority, and confidence as they come up against the tech revolution unfolding in their living rooms. We all know that deep connection with the people we love means everything to us. It's time to look with fresh eyes and an open mind at the disconnection we are experiencing from our extreme device dependence. It's never too late to put down the iPad and come to the dinner table. -- From book jacket.
The revolution in the living room -- Lost in connection: how the tech effect puts children's development at risk -- The brilliant baby brain: no apps or upgrades needed -- Mary had a little iPad: the wisdom of tradition, the wonder of tech, ages three to five -- Fast-forward childhood: when to push pause, delete, and play, ages six to ten -- Going, going, gone: Tweens, screens, and the perils of independence, ages eleven to thirteen -- Teens, tech, temptation, and trouble: acting out on the big (and little) screen -- Scary, crazy, and clueless: teens talk about how to be a go-to parent in the digital age -- The sustainable family: turning tech into an ally for closeness, creativity, and community.
Includes bibliographical references and index.
Keywords: Internet and families -- Social aspects -- United States; Technology and children -- Social aspects -- United States; Computers and families -- Social aspects -- United States; Digital media -- Social aspects -- United States; Parenting -- United States